2003
DOI: 10.1086/379245
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Point Sources in the Sombrero Galaxy: Very Soft Sources, the Globular Cluster/Low‐Mass X‐Ray Binary Connection, and an Overview

Abstract: We report on the population of point sources discovered during an 18.5 ks Chandra ACIS-S observation of the Sombrero galaxy. We present the luminosity function and the spectra of the six brightest sources, consider correlations with globular clusters (GCs) and with planetary nebulae, and study the galaxy's population of very soft sources. We detected 122 sources. Twenty-two sources are identified as very soft; of these, five appear to be classical luminous supersoft X-ray sources (SSSs), while 17 may belong to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
(63 reference statements)
2
28
0
Order By: Relevance
“…This trend already can be seen in the small Milky Way sample of LMXBs, but becomes much more evident in larger galaxies (e.g., Angelini et al 2001;Kundu et al 2002Kundu et al , 2007Di Stefano et al 2003;Kim et al 2006;Sivakoff et al 2007;Posson-Brown et al 2006). The physical mechanisms underlying this observational result are still unknown, although several possibilities have been put forward, including metallicity-dependent variations in the initial mass function (Grindlay 1987), the link between metallicity and the outer convective zones of stars (Ivanova 2006), and the effects of metallicity on radiation-induced stellar winds ( Maccarone et al 2004).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This trend already can be seen in the small Milky Way sample of LMXBs, but becomes much more evident in larger galaxies (e.g., Angelini et al 2001;Kundu et al 2002Kundu et al , 2007Di Stefano et al 2003;Kim et al 2006;Sivakoff et al 2007;Posson-Brown et al 2006). The physical mechanisms underlying this observational result are still unknown, although several possibilities have been put forward, including metallicity-dependent variations in the initial mass function (Grindlay 1987), the link between metallicity and the outer convective zones of stars (Ivanova 2006), and the effects of metallicity on radiation-induced stellar winds ( Maccarone et al 2004).…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, Fabbiano et al (2007) have recently shown that GCs in NGC 3379 lack low-luminosity LMXBs when compared to the field population, implying that the latter cannot have originated from GCs (see also Voss & Gilfanov 2007). To date, large populations of LMXBs have been found in X-ray observations of E/S0 galaxies over a wide range of luminosities (e.g., Sivakoff et al 2007;Kundu et al 2007) and in large disk galaxies such as M31, NGC 3115, and NGC 4594 (Fan et al 2005;Kundu et al 2003;Di Stefano et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some aspects of the LMXB properties in several of these galaxies have been analyzed in previous studies Di Stefano et al 2003;Sarazin et al 2003;Randall et al 2004;Kim et al 2006b). The X-ray properties of our sample are consistent with these studies in the areas that these analyses overlap.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…We find only one GC that is marginally in the blue population of NGC 4594. Given the higher contamination rate in the ground-based GC sample of Di Stefano et al (2003), it is possible that some of the ''blue'' GC LMXB candidates in their sample are contaminating background objects such as AGNs (also see x 3.5).…”
Section: Colors and Magnitudes Of Gcs Hosting Lmxbsmentioning
confidence: 99%
“…We take the distances to these galaxies from Tonry et al (2001). Partial results for all of these galaxies have been presented previously (ALM; Kundu et al 2003Kundu et al , 2004KMZ;Di Stefano et al 2003), and a detailed analysis with full source catalogs will be presented in future work (Kundu et al, in prep. ) In all, our sample includes 98 X-ray sources in 2276 globular clusters.…”
Section: Observationsmentioning
confidence: 99%